Manipulating Memory Associations Minimizes Avoidance Behavior - Wang, Jianqin; Smeets, Tom; Otgaar, Henry; Howe, Mark L. (Frontiers in Behavioral Neuroscience, 2021)
Memories of the past can guide humans to avoid harm. The logical consequence of this is if memories are changed, avoidance behavior should be affected. More than 80 years of false memory research has shown that people’s memory can be re-constructed or distorted by receiving suggestive false feedback. The current study examined whether manipulating people’s memories of learned associations would impact fear related behavior. A modified sensory preconditioning paradigm of fear learning was used. Critically, in a memory test after fear learning, participants received verbal false feedback to change their memory associations. After receiving the false feedback, participants’ beliefs and memories ratings for learned associations decreased significantly compared to the no feedback condition. Furthermore, in the false feedback condition, participants no longer showed avoidance to fear conditioned stimuli and relevant subjective fear ratings dropped significantly. Our results suggest that manipulating memory associations might minimize avoidance behavior in fear conditioning. These data also highlight the role of memory in higher order conditioning.